Co-designing a blueprint for spreading person-centered, Whole Health care to HIV specialty care settings: a mixed methods protocol - Sonia Rupcic; Ming Z. Tam; Kathryn L. DeLaughter; Allen L. Gifford; Anna M. Barker; Barbara G. Bokhour; Chris Xu; Eileen Dryden; Ekaterina Anderson; Guneet K. Jasuja; Jacqueline Boudreau; Jamie H. Douglas; et al. (BMC, 2024)
Abstract Background Since 2013, the Veterans Health Administration (VHA) has advanced a person-centered, Whole Health (WH) System of Care, a shift from a disease-oriented system to one that prioritizes "what matters most" to patients in their lives. Whole Health is predicated on patient-provider interactions marked by a multi-level understanding of health and trusted relationships that promote well-being. Presently, WH implementation has been focused largely in primary care settings, yet the goal is to effect a system-wide transformation of care so that Veterans receive WH across VHA clinical settings, including specialty care. This sort of system-wide cultural transformation is difficult to implement. Methods This three-aim mixed methods study will result in a co-designed implementation blueprint for spreading WH from primary to specialty care settings. Taking HIV specialty care as an illustrative case- because of its diverse models of relationships to primary care - to explore how to spread WH through specialty care settings. We will use the integrated Promoting Action on Research Implementation in Health Services (i-PARIHS) framework to organize quantitative and qualitative data and identify key determinants of WH receipt among Veterans living with HIV. Through a co-design process, we develop an adaptable implementation blueprint that identifies and matches implementation strategies to different HIV specialty care configurations. Discussion This study will co-design a flexible implementation blueprint for spreading WH from VHA primary care throughout HIV specialty care settings. This protocol contributes to the science of end-user engagement while also answering calls for greater transparency in how implementation strategies are identified, tailored, and spread.